Preparation and management of complications in prostate biopsies - Tyng,Chiang Jeng (2013)
Transrectal ultrasonography-guided biopsy plays a key role in prostate sampling for cancer detection. Among interventional procedures, it is one of the most frequent procedures performed by radiologists. Despite the safety and low morbidity of such procedure, possible complications should be promptly assessed and treated. The standardization of protocols and of preprocedural preparation is aimed at minimizing complications as well as expediting their management. The authors have made a literature review describing the possible complications related to transrectal ultrasonography-guided prostate biopsy, and discuss their management and guidance to reduce the incidence of such complications.